2002
DOI: 10.1063/1.1513465
|View full text |Cite
|
Sign up to set email alerts
|

Investigations into the fragmentation and ionization of highly excited La@C82

Abstract: Articles you may be interested inPhotodissociation of (SO2XH) Van der Waals complexes and clusters (XH = C2H2, C2H4, C2H6) excited at 32 040-32090 cm−1 with formation of HSO2 and X J. Chem. Phys. 140, 054304 (2014); 10.1063/1.4863445Mass spectrometry study of the fragmentation of valence and core-shell ( Cl 2p) excited CHCl 3 and CDCl 3 molecules J. Chem. Phys. 120, 9547 (2004); 10.1063/1.1701658 Formation of small lanthanum-carbide ions from laser induced fragmentation of La @ C 82We report the first measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Fragmentation processes which have been observed include the emission of neutral C 2 (evaporation), the emission of charged C 2 + (fission), and Coulomb explosion where molecular and atomic carbon ions are emitted. The fragmentation of endohedral fullerenes has been observed in experiments with femtosecond near-infrared lasers, nano-second visible lasers, synchrotron x-ray sources, and x-ray free-electron lasers [9,[22][23][24][25][26][27][28][29][30][31][32][33][34][35]. However, the studies regarding the fragmentation dynamics in endohedral fullerenes have mainly focused on neutral carbon dimer emission induced by single x-ray photons or single pulse lasers [29,30,32,34], or the formation of new chemical bonds [23,24,33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fragmentation processes which have been observed include the emission of neutral C 2 (evaporation), the emission of charged C 2 + (fission), and Coulomb explosion where molecular and atomic carbon ions are emitted. The fragmentation of endohedral fullerenes has been observed in experiments with femtosecond near-infrared lasers, nano-second visible lasers, synchrotron x-ray sources, and x-ray free-electron lasers [9,[22][23][24][25][26][27][28][29][30][31][32][33][34][35]. However, the studies regarding the fragmentation dynamics in endohedral fullerenes have mainly focused on neutral carbon dimer emission induced by single x-ray photons or single pulse lasers [29,30,32,34], or the formation of new chemical bonds [23,24,33].…”
Section: Introductionmentioning
confidence: 99%
“…The fragmentation of endohedral fullerenes has been observed in experiments with femtosecond near-infrared lasers, nano-second visible lasers, synchrotron x-ray sources, and x-ray free-electron lasers [9,[22][23][24][25][26][27][28][29][30][31][32][33][34][35]. However, the studies regarding the fragmentation dynamics in endohedral fullerenes have mainly focused on neutral carbon dimer emission induced by single x-ray photons or single pulse lasers [29,30,32,34], or the formation of new chemical bonds [23,24,33]. A few experiments observed the emission of the encaged atoms or molecules [22][23][24]29,33,35,36], but only the kinetic energy release (KER) of the encaged N atom from N@C 60 + and N@C 70 + has been measured [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…It has also been subject of several investigations in the gas phase [15][16][17][18][19][20][21][22][23][24]. In several of these studies, decay channels for highly excited La@C 82 and La@C 82 + were characterized, such as electron emission [19], fragmentation [16][17][18][19][20][21]23], and radiation [22]. However, in only one of these studies [24] it was attempted to determine the stability of La@C 82 + in a quantitative way, by measuring the activation energy, or "dissociation energy" D for the reaction:…”
Section: Introductionmentioning
confidence: 98%
“…It was among the first metallofullerenes to be isolated [13]; since then it has been characterized by a variety of physical methods (see [2][3][4][5]14] and references therein). It has also been subject of several investigations in the gas phase [15][16][17][18][19][20][21][22][23][24]. In several of these studies, decay channels for highly excited La@C 82 and La@C 82 + were characterized, such as electron emission [19], fragmentation [16][17][18][19][20][21]23], and radiation [22].…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of the ionization and fragmentation of endohedral fullerenes is not as comprehensive as for C 60 , due to extra theoretical and experimental complications. Nevertheless, a few studies regarding the fragmentation dynamics in endohedral fullerenes have been carried out, focusing on neutral carbon dimer emission induced by single Xray photons or single pulse optical lasers [22][23][24][25], or the formation of new chemical bonds between atoms from the cage and the enclosed species [9,[26][27][28]. Recently, we found that the endohedral fullerene's internal energy plays an important role in the fragmentation of X-ray excited Sc 3 N@C 80 [29].…”
Section: Introductionmentioning
confidence: 99%